Relayout Gudang Produk Jadi dengan Pendekatan Class- Based Storage di PT. XYZ - Septia, Wulan; Wati, Putu Eka Dewi Karunia (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Warehouse efficiency involves the optimal management of space and time. PT. XYZ is a manufacturing company that produces pipes and fittings; however, it has not yet implemented a product classification system or location labeling, resulting in inefficient item retrieval processes. This study aims to redesign the warehouse layout using a class-based storage approach combined with ABC analysis. The classification results show that Spr products consist of Class A (68.49%), B (20.55%), and C (10.96%), while Exc products consist of Class A (69.47%), B (20%), and C (10.53%). Products with diameters ranging from 5/8” to 4” are recommended to be stored on racks, while those with diameters greater than 4” should be placed on the floor. This layout is expected to improve the efficiency of the item search and retrieval process in the warehouse